1989
DOI: 10.1088/0022-3727/22/11/005
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic properties of conducting polyanilines

Abstract: A study has been made of the electrochromic behaviour of polyaniline films of potential use in passive display devices, and a preliminary examination of the properties of substituted polyanilines has also been carried out. Films of 'emeraldine-type' conducting polyanilines have been grown electrochemically from aqueous solutions onto glass substrates coated with gold or indium tin oxide. The authors have studied the electrochemistry of their redox reactions in acidic media to examine the kinetics and reversibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(22 citation statements)
references
References 8 publications
2
17
0
3
Order By: Relevance
“…Kemudian ditemukan sifat elektrokromik pada bahan organik yaitu polianilin [7]. Polianilin memiliki sifat yang baik antara lain kontras warna yang tajam, siklus pemakaian yang awet [6], stabil [7], pada prinsipnya mudah disiapkan [8] dan mudah diperoleh di pasar lokal. Penelitian sudah dilakukan terhadap polianilin dengan 0,001M H 2 SO 4 dan 0,01M H 2 SO 4 [9], 0,1M HCl [7] dan 1,0M HCl [8,10].…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Kemudian ditemukan sifat elektrokromik pada bahan organik yaitu polianilin [7]. Polianilin memiliki sifat yang baik antara lain kontras warna yang tajam, siklus pemakaian yang awet [6], stabil [7], pada prinsipnya mudah disiapkan [8] dan mudah diperoleh di pasar lokal. Penelitian sudah dilakukan terhadap polianilin dengan 0,001M H 2 SO 4 dan 0,01M H 2 SO 4 [9], 0,1M HCl [7] dan 1,0M HCl [8,10].…”
Section: Pendahuluanunclassified
“…Warna yang teramati secara visual dalam jangkauan tegangan antara −0.2 dan 1.0 V adalah kuning transparan, hijau muda, hijau, biru dan violet. Pada Gambar 3 dapat dilihat bahwa film polianilin menghasilkan puncak-puncak oksidasi di sekitar 0.25, 0.45 dan 0.7 V yang ditandai dengan huruf A, B dan C, sedangkan puncak reduksi berada di sekitar 0.0 , 0.35 dan 0.6 V yang ditandai dengan D, E dan F. Puncakpuncak ini disebabkan oleh peristiwa alih (transfer) muatan [8]. Pengaruh konsentrasi asam dapat diamati pada rapat arus yang berharga sampai sekitar 2.5 mA/cm 2 , lebih tinggi dari pada sekitar 0.1 mA/cm 2 yang diperoleh [9] dengan 0.001M dan 0.01M H 2 SO 4 .…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…This redox change results in a change of material properties such as conductivity [1], electrochromism [2], and wettability [3,4]. The ion transport during this redox switching has also been used in drug release applications [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Last year we reported the preparation of conductive PAn/(styrene-butadiene-styrene)triblkock copolymer (SBS) composites in one-step via in situ emulsion polymerization. 18 Foot and Simon 19 first reported that PAn can be used in electrochromic device due to the change of colors during a voltammetric cycle at pH 0 -1 media. Bernard and Hugot-LeGoff 20 showed that a weakly acidic electrolyte solution (at pH 3 but not pH 5) is best suitable for electrochromic purpose of PAn.…”
Section: Introductionmentioning
confidence: 99%